Circulatory disease pathogenesis - E. N. Vorobyeva; I. V. Osipova; R. I. Vorobyev; Yu. V. Treshutina (Кардиоваскулярная терапия и профилактика, 2006)
The review is devoted to biological role of reactive oxygen forms, generated in various cells of all healthy organisms, and performing, due to their high chemical reactivity and short lifetime, vital function of signal intracellular transduction and intercellular mediation, realizing immediate and delayed adaptation of tissue metabolism, circulatory system included. In excessive amount of these molecules, their moderating function transforms into damaging oxidation and destruction of tissue lipids, proteins and nucleic acids. This concept is supported by numerous clinical data on substantial increase in tissue and plasma levels of active oxygen forms and oxidative cellular biopolymer damage products among patients with essential arterial hypertension, atheroscleroisis, coronary heart disease and myocardial infarction. The leading pathogenetic role is played by local and/or systemic hyperproduction of superoxide and hydroxide radicals, hydroperoxide, NO, peroxinitrite and other active oxygen forms.